Tritium content in lichens in the emergency protective action planning zone of the Belarusian Nuclear Power Plant - Averyn, Viktar; Tsurykau, Andrei; Mikhailov, Andrey (Journal of the Belarusian State University. Ecology, 2026)
Lichens play a crucial role in environmental monitoring and assess the impact of industrial emissions. They are sensitive to a wide range of pollutants and reflect air quality and climate change. Lichens allow us to track the dynamics of pollutant accumulation, making them the most sensitive bioindicators of air pollution at the regional level. As part of the biomonitoring system for inorganic pollutants in the emergency protective planning zone of the Belarusian Nuclear Power Plant, tritium levels in the thalli of the corticolous lichen Xanthoria parietina were determined. Thalli sampling was conducted within 16 sample plots established for long-term environmental monitoring, taking into account the occurrence and biomass of Xanthoria parietina in the emergency protective planning zone of the Belarusian Nuclear Power Plant. Tritium content in these samples was analyzed using a Tri-Carb 4810 spectrometer. Studies of tritium content in Xanthoria parietina thalli collected within the emergency protective planning zone of the Belarusian NPP revealed that the specific activity of this radionuclide in all samples was below the detection limit of the liquid scintillation spectrometry method used (20 Bq/kg dry weight). Trace amounts of tritium – 22 Bq/kg – were detected in the single lichen sample. The data obtained indicate that tritium emissions into the atmospheric air in the study area are either absent or below the detection limit of current analytical methods. Tritium activity in the ground-level air during the observation period did not exceed background levels typical for areas not affected by nuclear fuel cycle facilities. The contribution of emissions from the Belarusian NPP to tritium pollution of the atmospheric air is negligible and does not significantly affect the radioecological situation in the region. Continued monitoring studies using sample enrichment methods to detect ultra-low tritium concentrations in environmental samples are recommended.